Human resource development and organizational values - Hassan, Arif (Emerald Group Publishing Limited, 2007)
Purpose – Organizations create mission statements and emphasize core values. Inculcating those values depends on the way employees are treated and nurtured. Therefore, there seems to be a strong relationship between human resource development (HRD) practices and organizational values. The paper aims to empirically examine this relationship. Design/methodology/approach – The study measured employees’ rather than management perspective. A sample of 239 employees from eight organizations responded to a questionnaire which measured the effectiveness of employee development practices and cherished organizational values. Findings – HRD practices like potential appraisal and promotion, learning/training, performance guidance and development were positively related to organizational values of collaboration, creativity,quality, delegation, and humane treatment. However, performance appraisal system, career planning, and contextual analysis variables were negatively associated with values such as trust and creativity. Research limitations/implications – The study was exploratory in nature. Further studies are needed on a larger sample to examine why some HRD practices like performance appraisal, career planning and contextual analysis contributed negatively to organizational values such as trust and creativity. Practical implications – The result of the study can be useful in designing effective employee development programs that promote cherished organizational values. Originality/value – Little empirical knowledge exists on HRD and organizational values linkages in the context of transitional economies like Malaysia. The paper makes a modest attempt to fill the gap.